Gene expression profiling and endothelin in acute experimental pancreatitis - Oz, Helieh S (Baishideng Publishing Group Co., Limited, 2012)
AIM: To analyze gene expression profiles in an experimental pancreatitis and provide functional reversal of hypersensitivity with candidate gene endothelin-1 antagonists. METHODS: Dibutyltin dichloride (DBTC) is a chemical used as a polyvinyl carbonate stabilizer/catalyzer, biocide in agriculture, antifouling agent in paint and fabric. DBTC induces an acute pancreatitis flare through generation of reactive oxygen species. Lewis-inbred rats received a single i.v. injection with either DBTC or vehicle. Spinal cord and dorsal root ganglia (DRG) were taken at the peak of inflammation and processed for transcriptional profiling with a cDNA microarray biased for rat brain-specific genes. In a second study, groups of animals with DBTC-induced pancreatitis were treated with endothelin (ET) receptor antagonists [ET-A (BQ123) and ET-B BQ788)]. Spontaneous pain related mechanical and thermal hypersensitivity were measured. Immunohistochemical analysis was performed using anti-ET-A and ET-B antibodies on sections from pancreatic tissues and DRG of the T10-12 spinal segments. RESULTS: Animals developed acute pancreatic inflammation persisting 7-10 d as confirmed by pathological studies (edema in parenchyma, loss of pancreatic architecture and islets, infiltration of inflammatory cells, neutrophil and mononuclear cells, degeneration, vacuolization and necrosis of acinar cells) and the pain-related behaviors (cutaneous secondary mechanical and thermal hypersensitivity). Gene expression profile was different in the spinal cord from animals with pancreatitis compared to the vehicle control group. Over 260 up-regulated and 60 down-regulated unique genes could be classified into 8 functional gene families: circulatory/acute phase/immunomodulatory; extracellular matrix; structural; channel/receptor/transporter; signaling transduction; transcription/translation-related; antioxidants/chaperones/heat shock; pancreatic and other enzymes. ET-1 was among the 52 candidate genes up-regulated greater than 2-fold in animals with pancreatic inflammation and visceral pain-related behavior. Treatments with the ET-A (BQ123) and ET-B (BQ-788) antagonists revealed significant protection against inflammatory pain related mechanical and thermal hypersensitivity behaviors in animals with pancreatitis (P < 0.05). Open field spontaneous behavioral activity (at baseline, day 6 and 30 min after drug treatments (BQ123, BQ788) showed overall stable activity levels indicating that the drugs produced no undesirable effects on normal exploratory behaviors, except for a trend toward reduction of the active time and increase in resting time at the highest dose (300 μmol/L). Immunocytochemical localization revealed that expression of ET-A and ET-B receptors increased in DRG from animals with pancreatitis. Endothelin receptor localization was combined in dual staining with neuronal marker NeuN, and glia marker, glial fibrillary acidic protein. ET-A was expressed in the cell bodies and occasional nuclei of DRG neurons in naïve animals. However, phenotypic expression of ET-A receptor was greatly increased in neurons of all sizes in animals with pancreatitis. Similarly, ET-B receptor was localized in neurons and in the satellite glia, as well as in the Schwann cell glial myelin sheaths surrounding the axons passing through the DRG. CONCLUSION: Endothelin-receptor antagonists protect against inflammatory pain responses without interfering with normal exploratory behaviors. Candidate genes can serve as future biomarkers for diagnosis and/or targeted gene therapy.